On diasporic identities construction: case study on "Hinduness" (Tempo e Argumento, 2010)
The complexity of cultural identities construction – in a context of increasingly intense and diverse migratory flows, characteristic of contemporary globalization processes – is related to the coexistence of trends toward homogeneity and heterogeneity, as well as to the possibility of constructing such identities from the homeland or from the host societies. Through a case study on Hindutva (Hinduness), a Hindu diasporic identity, we intend to look into how contemporary Hindu nationalist organizations represent migration, stressing particularly: (1) the relationship between national and transnational dimensions in a diasporic identity constructed from the homeland; (2) the religious definition of such diasporic identity.
Keywords: diasporas; cultural identities; migratory mobility; India; contemporary hindu nationalism